P0890EFFICACY AND SAFETY OF CINACALCET IN CHINESE MAINTENANCE HEMODIALYSIS PATIENTS WITH DIFFERENT STAGES OF SECONDARY HYPERPARATHYROIDISM: INTERIM ANALYSIS RESULTS OF ACTIVE STUDY. (6th June 2020) - Jiang, Aili; Fu, Ping; Xiao, Guanqing; Ye, Jian-ming; Liu, Zhang-suo; Chen, Xiao-Nong; Ni, Zhaohui; Ling, Yisheng; He, Qiang; Chen, Jing; Chen, Chaosheng; Hao, Li; et al.
Abstract: Background and Aims: Chronic kidney disease (CKD) is a major public health issue worldwide including in China. One of the most common complication in advanced Chronic kidney disease (CKD) is secondary hyperparathyroidism (SHPT). Reports show higher risk of bone fracture, cardiovascular events and all-cause mortality is associated with uncontrolled SHPT in patients with CKD. Cinacalcet, a calcimimetic agent was reported to reduce iPTH levels without Ca increase in patients with SHPT previously. However there has been no large-cohort study and stratified analysis of cinacalcet based on the level of iPTH in China. Moreover, the optimal therapeutic doses of cinacalcet with mild-to-severe SHPT is remaining unknown. ACTIVE study is an IV, open-label, multicenter clinical trial aimed to: (1) evaluate the efficacy and safety of cinacalcet in maintenance hemodialysis patients with mild-to-severe SHPT; (2) explore optimal combinations therapy with cinacalcet and other agents for treating patients with CKD-mineral and bone disorder. (3) investigate the benefit of long-term, continuous medication with cinacalcet in the real-world setting. Method: The study design was reported on 2019 ASN. Key inclusion criteria were a baseline iPTH ≥300 pg/mL with life expectancy of ≥2 years, and ≥12 weeks of maintenance dialysis (three dialysis sessions per week) prior to enrollment. The enrollments were grouped based on their iPTH level as having mild (300-600 pg/mL), moderate (600-900 pg/mL) or severe (≥900 pg/mL). Patients initiated treatment with cinacalcet orally at a starting dose of 25 mg once daily (qd). The primary efficacy endpoint is the proportion of patients achieving iPTH targets (iPTH between 150-300pg/mL) at 20 and 32 weeks after the initiation of cinacalcet treatment. Adverse events and serious adverse events were recorded. An interim analysis was scheduled as 375 patients completed 32 weeks visit. Results: 911 patients were recruited and of 750 eligible patients, 275 were identified as mild, 224 were considered as moderate and left 251 were grouped as severe SHPT. The study flowchart of 375 patients including mild(127), moderate(106) and severe(142) SHPT for interim analysis was shown in Fig 1. The baseline results including demographic and biomarkers level were reported on 2019 ASN. After 4 weeks' cinacalcet treatment, serum PTH decreased in all three group, while extremely remarkable in the severe SHPT group. Interim analysis results revealed that the proportion of patients achieving iPTH target (150-300 pg/mL) at 20 wk visit among mild, moderate and severe groups were 38.61% (39/101), 30.11% (28/93) and 10.91% (12/110) respectively. The proportion of patients achieving iPTH target at 32 wk visit in 3 groups increased to 44.68% (42/94), 27.27% (24/88) and 14.56% (15/103) respectively (Table.1). The trends of the proportion of patients achieving iPTH target increased in all 3 different groups (Fig.2). The safety analysis showed the most common treatment-related AE in top 3 including hypocalcemia, hyperlipidemia, and loss of appetite. In vital signs, electrocardiogram (ECG) and laboratory examination of descriptive analysis, found no obvious safety tips. This study is sponsored by Kyowa Hakko Kirin (China) Pharmaceutical Co., Ltd. The analysis is still ongoing and results will be released at EDTA meeting this year. Conclusion: Oral cinacalcet HCl was effective and safe in reducing iPTH in patients receiving HD with mild-to-severe SHPT.